2000
DOI: 10.1161/01.cir.102.25.3060
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Parameters and Mortality in Patients With Chronic Heart Failure

Abstract: sTNF-R1 was the strongest and most accurate prognosticator, independent of established markers of CHF severity. Assessment of sTNF-R1 may be useful in identifying patients who are at high risk of death and in monitoring patients undergoing anti-TNF-alpha treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
238
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 697 publications
(254 citation statements)
references
References 24 publications
9
238
0
7
Order By: Relevance
“…Because this variable was skewed to the right, we created a binary variable using the cut point of ≥7 for the high deficiency category. This value was chosen because 25% of the sample had a score at or above this level; this type of dichotomy has been used previously with skewed clinical predictors of heart failure outcomes 25. Participants with fewer micronutrient deficiencies were classified as no to moderate deficiency .…”
Section: Methodsmentioning
confidence: 99%
“…Because this variable was skewed to the right, we created a binary variable using the cut point of ≥7 for the high deficiency category. This value was chosen because 25% of the sample had a score at or above this level; this type of dichotomy has been used previously with skewed clinical predictors of heart failure outcomes 25. Participants with fewer micronutrient deficiencies were classified as no to moderate deficiency .…”
Section: Methodsmentioning
confidence: 99%
“…RELAX included S‐HFpEF patients while DOSE and ROSE included acutely decompensated HF (ADHF) patients with both HFrEF and HFpEF. IL‐6, TNF‐α, and hs‐CRP were selected because of the long‐standing experience with their use in HF10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and PTX3 because of its association with vascular inflammation21 and ability to risk‐stratify HF patients. Each trial was approved by the Institutional Review Board at each participating site, and all patients provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have revealed a significant correlation between elevations in blood levels of pro‐inflammatory biomarkers such as tumor necrosis factor alpha (TNF‐α), C‐reactive protein (CRP),interleukin 6 (IL‐6), and HF severity and prognosis 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. Recently, pentraxin 3 (PTX3), an acute‐phase reactant member of the CRP super family expressed by a variety of cell types in response to various inflammatory stimuli21 and thought to be a marker of vascular inflammation, was found to facilitate risk stratification of HF patients 22, 23, 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they found that tumor necrosis factor alpha levels were markedly increased in patients with end‐stage heart failure and renal impairment without being correlated to cardiac output or ventricular filling pressure, thus indicating prognosis rather than cardiac function. Several studies were since able to show that increased cytokine levels were related to a poor prognosis in patients with heart failure 4, 5, 6, 7…”
Section: Procalcitonin As a Prognostic Marker In Heart Failurementioning
confidence: 99%